2005
DOI: 10.1097/01.aids.0000166093.16446.c9
|View full text |Cite
|
Sign up to set email alerts
|

Early exclusive breastfeeding reduces the risk of postnatal HIV-1 transmission and increases HIV-free survival

Abstract: EBF may substantially reduce breastfeeding-associated HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
347
3
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(389 citation statements)
references
References 18 publications
25
347
3
14
Order By: Relevance
“…Breast milk viral load is an important determinant of postnatal HIV transmission [3,[10][11][12][13] and is associated with high plasma viral load [14,15], advanced HIV disease [16,17], and mastitis [7,10]. Increases in mammary epithelial permeability which accompanies weaning in animals [18,19] and humans [20,21] may also increase breast milk viral load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast milk viral load is an important determinant of postnatal HIV transmission [3,[10][11][12][13] and is associated with high plasma viral load [14,15], advanced HIV disease [16,17], and mastitis [7,10]. Increases in mammary epithelial permeability which accompanies weaning in animals [18,19] and humans [20,21] may also increase breast milk viral load.…”
Section: Discussionmentioning
confidence: 99%
“…A partial solution to this problem was suggested by the preliminary observation that exclusive breastfeeding conferred less risk of breast milk transmission than mixed feeding [2,3]. This has led to calls for early cessation of exclusive breastfeeding to provide the young infant some of the healthful immune and nutritive benefits of breast milk while minimizing the duration of exposure to HIV [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence now exists illustrating the role of exclusive breast-feeding (EBF) in minimizing transmission risk of HIV while promoting child health, resulting in greater HIV-free child survival (5)(6)(7) . Recently, an African-based prospective study with feeding data on 1276 infants found a low transmission risk (4 %) following 6 months of EBF, with mortality at 3 months more than double in formula-fed babies compared with EBF infants (8) .…”
mentioning
confidence: 99%
“…Seven countries have reported results (37)(38)(39)(40)(41)(42)(43)(44) from the surveillance of transmitted HIV drug resistance in geographical areas where antiretroviral therapy was first used within the country (Table 2.3). All reported less than 5% transmitted resistance to all antiretroviral drugs and drug classes.…”
Section: Prevention and Assessment Of Hiv Drug Resistancementioning
confidence: 99%